1994
DOI: 10.1021/bi00187a036
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Bombolitin III with Phospholipid Monolayers and Liposomes and Effect on the Activity of Phospholipase A2

Abstract: This study is focused on the characterization of the interaction of the amphiphilic peptide bombolitin III (from the bumblebee Megabombus pennsylvanicus) with phospholipid monolayers and vesicles. It is shown that due to the amphiphilic character of its alpha-helical conformation this water-soluble peptide is able to interact in an ordered fashion with phospholipid organized structures. Depending on the temperature, the subphase, and the particular phosphatidylcholine used, the mixed peptide-phospholipid monol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 31 publications
5
20
0
Order By: Relevance
“…Enzyme activities that are affected by the phase boundaries of lipid domains may provide a means whereby lipid composition itself is regulated through enzyme activity. Although this possibility has not been proposed previously to the best of our knowledge, pub lished experimental work [21][22][23][24][25][26] on the action of en zymes on lipid membranes is not inconsistent with this hypothesis.…”
mentioning
confidence: 86%
“…Enzyme activities that are affected by the phase boundaries of lipid domains may provide a means whereby lipid composition itself is regulated through enzyme activity. Although this possibility has not been proposed previously to the best of our knowledge, pub lished experimental work [21][22][23][24][25][26] on the action of en zymes on lipid membranes is not inconsistent with this hypothesis.…”
mentioning
confidence: 86%
“…The use of the Langmuir method allows for a precise and continuous control of such parameters as molecular packing, physical state, lateral pressure, composition and quality of the surface. In particular, mixed monolayers composed of constituents of biological membranes, such as phospholipids, sterols and glycolipids, provide a highly informative approach for studying intermolecular interactions between membrane components, usually phospholipids, and biomolecules, for example, various drugs [2][3][4][5], hormones [6,7], enzymes [8][9][10][11], proteins [12][13][14][15][16][17][18][19][20][21], etc. Such investigations may be of much help in elucidating a mode of action of many physiological active compounds [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high affinity of all bombolitins toward micelles, monolayers and liposomes, it seems resonable to suppose that these peptides influence the activity of PLA, by altering the physical state of the aggregated substrate. This hypothesis was further substantiated by our recent investigation on the interaction of bombolition I11 with phospholipid monolayers and liposomes 30). By the Langmuir balance technique, coupled with epifluorescence microscopy, it was shown that the peptide forms phase-separated peptide domains at the air-water interface, with consequent alteration of the organization of the lipid monolayer.…”
Section: Discussionmentioning
confidence: 76%